Assessing the relationship between coral cover and coral recruitment in the degraded ecosystems of Sempu Nature Reserve, East Java, Indonesia - ANDIK ISDIANTO; RIDHA AYU WIBOWO; AMELINDA VIVIAN KUDRATI; DIAN ALIVIYANTI; MUHAMMAD ARIF ASADI; CITRA SATRYA UTAMA DEWI; ARIEF SETYANTO; TRI DJOKO LELONO; AGUS TUMULYADI; LISA NUR HIDAYAH; AULIA LANUDIA FATHAH; BERLANIA MAHARDIKA PUTRI; NOVAR KURNIA WARDANA; SUPRIYADI SUPRIYADI; OKTIYAS MUZAKY LUTHFI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Isdianto A, Wibowo RA, Kudrati AV, Aliviyanti D, Asadi MA, Dewi CSU, Setyanto A, Lelono TD, Tumulyadi A, Hidayah LN, Fathah AL, Putri BM, Wardana NK, Supriyadi, Luthfi OM. 2024. Assessing the relationship between coral cover and coral recruitment in the degraded ecosystems of Sempu Nature Reserve, East Java, Indonesia. Biodiversitas 25: 3075-3083. The long-term survival of coral ecosystems requires the existence of coral recruitment variables that function as agents for future coral generations. The efficacy of this recruitment is crucial for the coral ecology in Sempu Waters, which is renowned for its ongoing loss in coverage. This research aims to determine hard coral cover, the number of coral recruits, and the correlation between hard coral cover and the number of coral recruits. Data was collected using the underwater photo transect method, a widely accepted and reliable technique for assessing coral cover and diversity, at five research stations during 3 observation periods (December 2022, February 2023, and April 2023) and then analyzed using pearson correlation to determine the relationship between the percentage of coral cover and the number of coral recruits. The results show that the coral cover of the Sempu Strait is classified as damaged and has decreased for 3 consecutive months, namely 14.28, 13.92, and 12.57%, and only 22 coral recruits were found in total with 6 identified genera, including Seriatopora, Porites, Pocillopora, Goniastrea, Pavona, and Acropora. The correlation between hard coral cover and coral recruits shows a positive relationship and a fragile level of closeness (r = 0.1119). The availability of stable substrates for recruitment, such as Dead Coral with Algae (DCA), Dead Coral (DC), and Rock (RK), can increase the potential for successful recruitment. However, coral recruits in the Sempu Strait also face competition from other biota, such as macroalgae and adult corals themselves.